Biodegradation of acrylamide by a newly isolated Bacillus sp. strain ZK34 - Kusnin, Norzila (2015)
Acrylamide is a toxic and carcinogenic compound which may cause cancer and genetic mutation, and also irritation to the skin and respiratory tract. The main sources of acrylamide pollution are the release of monomer residues from polyacrylamide which are widely used for water treatment and from the formulation of herbicide glyphosate. To overcome this problem, a potent and efficient acrylamide-degrading bacterium has been isolated from agricultural soil. The isolate was tentatively identified as Bacillus sp. strain ZK34 based on 16S rRNA molecular phylogeny and was deposited at the GenBank under the accession number KC433533. Bacillus sp. strain ZK34 grew optimally in the range of pH 7.0 and pH 8.0, and at 28°C. The test on effects of carbon sources on the growth of the bacterium was carried out using carbon sources such as glucose, sucrose, fructose, lactose, maltose, mannitol, citric acid, dextrin and glycerol at the initial concentration of 1.0% (w/v) with acrylamide as the sole nitrogen source. The results showed that glucose was the best carbon source for bacterium growth. The effects of different aliphatic amides on the growth of strain ZK34 using 1.0% (w/v) glucose as the carbon source showed that acrylamide, propionamide, methacrylamide,nicotinamide, and acetamide supported growth with increasing assimilative capability from methacrylamide to propionamide while 2-loroacetamide did not support growth. The optimum concentration of acrylamide for the growth of Bacillus sp. strain ZK34 was at 0.5 g/L. Bacillus sp. strain ZK34 could degrade 0.5 g/L of acrylamide in three days of incubation with concomitant cell growth. Strain ZK34 was immobilized in gellan gum and the degradation of acrylamide was compared between freely-suspended and immobilized cells. Optimization for immobilization procedures found 0.75% (w/v) of gellan gum, 300 beads/100 mL of BSM and 3 mm of bead size gave optimum degradation of acrylamide. Bacillus sp. strain ZK34 which has been immobilized in gellan gum beads showed enhanced degradation of elevated concentrations of acrylamide (3.0 g/L) compared to the free cells (2.0 g/L) and could be reused for at least 8 complete cycles. Kinetics study revealed that immobilized cells suited Yano model which indicated the acrylamide was not toxic to the cells even though the acrylamide concentration was high, while free cells fitted to Luong kinetic model where acrylamide was toxic whether at low or high concentrations. Heavy metals and pesticides showed less inhibition of acrylamide degradation in immobilized cells than the free cells. The outcome of this study will contribute to additional knowledge on a new source of more efficient microbe in acrylamide degrading process and has high potential to be used in the contaminated sites.